2016
DOI: 10.1080/01694243.2016.1259758
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fracture resistance of endodontically treated premolar teeth restored with a direct layered fiber-reinforced composite post and core

Abstract: Methods for restoring endodontically treated teeth fall short of restoring the physiologic mechanical properties. Fracture of endodontically treated teeth is a common type of clinical failure. New treatment modalities or perfected versions of existing treatment concepts need to be tested to find a biomimetic solution. A novel method of restoring endodontically treated teeth is presented and compared in vitro with currently accepted restorative methods. Seventy-two extracted and endodontically treated maxillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 59 publications
4
26
2
Order By: Relevance
“…This in line with Forster et al., who studied different designs of restoring endodontically‐treated premolars, and found that the application of direct‐layered SFRC as post and core in endodontically‐treated premolars performed statistically similarly in the studied conditions as natural teeth and higher than all other tested restoration designs . They also emphasized that the direct‐layered SFRC‐based biomimetic composite restoration is a promising alternative technique in restoring ETT . Garoushi et al.…”
Section: Resultssupporting
confidence: 79%
“…This in line with Forster et al., who studied different designs of restoring endodontically‐treated premolars, and found that the application of direct‐layered SFRC as post and core in endodontically‐treated premolars performed statistically similarly in the studied conditions as natural teeth and higher than all other tested restoration designs . They also emphasized that the direct‐layered SFRC‐based biomimetic composite restoration is a promising alternative technique in restoring ETT . Garoushi et al.…”
Section: Resultssupporting
confidence: 79%
“…This was partly confirmed by Forster et al, and Fráter et al, in endodontically treated premolar teeth with class I cavity. In those studies, the directly layered SFRC post and core groups displayed promising performance in matter of fracture behavior 22,23) .…”
Section: Introductionmentioning
confidence: 98%
“…Also, these results exceeded those of other studies. According to Nordahl et al 29 the mean fracture resistance of e.max lithium disilicate crowns of posterior molars of thickness 1.5 mm was 1,431 N while according to Yu et al 22 it was 1827.3 N. This can be attributed to the exposure of crowns in both studies to artificial aging before loading until fracture. The exposure of the crowns to aging was stated in various investigations to diminish the resultant fracture loads significantly 29,30 .…”
Section: Discussionmentioning
confidence: 92%
“…Five different modes were observed and categorized as restorable or non-restorable according to their relation to the cemento-enamel junction (CEJ). A fracture that ends before CEJ, implying that even after the occurrence of fracture, the tooth can be saved is a restorable one, while fractures that are non-restorable extend beyond CEJ and extraction of the tooth is expected 22 . The extensions of the cracks were verified by SEM ( Figure 4).…”
Section: Fractographic Analysis Of Fractured Samplesmentioning
confidence: 99%